The predual space of a JBW*-triple - Rakhimov, Abdugafur Abdumadjidovich (Eurasian Mathematical Journal, 2014)
In the paper JB*-triples which are dual Banach spaces are considered as analogues of JBW*-algebras. For JBW*-triples an analogue of the classical theorem of Vitali–Hahn–Saks on convergent sequences of measures and a theorem on weak compactness of a set of normal functionals are proved.